PERANCANGAN WEB PORTAL PEMANTAU PEMILUKADA SERENTAK 2017 - Desy Puspa Rahayu; Wanda Gusdya Purnama; Ahnand Hafidz (POLITEKNIK PIKSI GANESHA, 2020)
Good governance can produced by a solid, responsible, efficient and honest government. To realize good governance, information system is needed to reach civilians. Indonesia renowned for a culture of mutual cooperation named “gotong-royong” and we pride of that. With the utilization of cyber community and crowdsourcing, Indonesian will be able to share information about politicians and even able to determine government policy in a way. To be able to determine government policy, the community should be part of a partnership model, called Quadruple Helix Partners. The Quadruple Helix Partnership is a balance relationship between government, universities, corporates, and the civilian. Development of this mayor/governor election monitoring web portal is inspired from another past product, named Idun demokrasi (Indonesia united demokrasi), which focused in general and presidential election. The Idun demokrasi system is an open information system platform using crowdsourcing approach.